Managerial Skills Development of Buah Ketakasi Cooperative: Improvement of the Quality Management System - Soepeno, Bambang; Puji, Rully Putri Nirmala; Triyanto, Jefri Rieski; Prasetyo, Guruh (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Buah Ketakasi is a cooperative founded by a community of coffee farmers in Jember district. Initially, the cooperative business unit involved was coffee agribusiness with 64 permanent members and 12 extraordinary members. The cooperative business unit expanded into coffee industrial agriculture, chicken and goat farm, dragon fruit cultivation, and organic fertilizer production. The number of permanent members has also increased to 182 people and extraordinary members to 300 people. This cooperative had problems including planning work programs, organizing resources, division of work, implementing work programs, monitoring and evaluating them. The offered solution to solving managerial problems of the cooperative was a mentoring program on how to plan a work program; how to organize resources, division of work, strategies for implementing work programs and monitoring-evaluation up to the reporting.